The crosstalk between probiotics and T cell immunity - Liu, Yuanyuan; Cao, Xu; Liu, Hongwei; Zhang, Wencan (Frontiers in Immunology, 2025)
Probiotic supplementation is one of the most widely well-recognized approaches for health maintaining. Distinct probiotics have been experimentally and mechanically investigated for their possible effectiveness in treating autoimmune disease, metabolic diseases, and cancer immune therapy, showing extensive and promising therapeutic potential. Focusing on the T cell mediated responses and diseases, this review specifically aims to elucidate the intricate crosstalk between probiotic microorganisms and T cells, exploring how probiotics modulate the differentiation, activation, proliferation, and functional states of different T cell subsets, such as CD4+ T cells and CD8+ T cells, thereby influencing the overall immune response and immune homeostasis. By revealing this crosstalk, we aim to uncover the potential of probiotics in immune regulation and disease prevention, providing valuable insights for developing novel therapeutic strategies and preventive measures leveraging the probiotics-T cell axis.